(untitled) (Innovative professional education, 2024)
The rebuilding of Ukraine is a unique opportunity to implement the world’s best practices. The article presents the results of a study on how the combination of digital technologies and sustainable development principles can change the construction industry in Ukraine and train qualified specialists to implement ambitious projects.